High hydrostatic pressure enhanced the growth of deep-sea Thermococcus aciditolerans by promoting the reduction of elemental sulfur - Jiao, Ze-Xi; Li, Xue-Gong; Zhang, Wei-Jia; Zhang, Guan-Yuan; Bai, Shi-Jie; Fu, Ling; Wu, Long-Fei (Frontiers in Microbiology, 2025)
Thermococcus species are ubiquitously distributed across both shallow and deep-sea hydrothermal vent ecosystems. Elemental sulfur (S°) reduction plays a pivotal role in their energy metabolism. While extensive characterization of the MBS and MBH pathways, along with their SurR-dependent regulatory network, has been established in shallow-water model strains, understanding of the high hydrostatic pressure (HHP) and sulfur-responsive regulation of these pathways in deep-sea Thermococcus lineages remains limited. In this study, we investigated the effects of HHP on both growth and S° reduction in the deep-sea SY113 strain, as well as its regulatory impact on mbs and mbh expression. Our results demonstrate that HHP enhances both S° reduction and growth in SY113 strain, independent of the general regulator SurR. Genetic disruption of mbsL significantly impaired H2S production and growth under HHP conditions, establishing the essential role of S° reduction in HHP adaptation. Furthermore, disrupted mbhL1 gene confirmed that a single MBS complex is sufficient to maintain pressure-stimulated growth. The gene expression analysis revealed that the expression of mbsL gene is primarily promoted by S°, while the expression of mbhL1 gene is induced by HHP. Moreover, the expression of these genes exhibits correlation. Additionally, we found that the expression of mbsL gene, mbhL1 gene, and mbhL2 gene in SY113 strain is not only regulated by SurR, and HHP also plays a role in modulating the expression of these genes. Overall, the sulfur responsive regulation of gene expression in SY113 strain distinguishes from that in the shallow model strains, which implies an adaptive strategy for Thermococcus species used to dwell in the deep-sea hydrothermal vent.